2019
DOI: 10.1212/wnl.0000000000006669
|View full text |Cite
|
Sign up to set email alerts
|

Prediagnostic plasma branched-chain amino acids and the risk of amyotrophic lateral sclerosis

Abstract: Objective To assess whether prediagnostic levels of plasma branched-chain amino acids (BCAAs) are associated with amyotrophic lateral sclerosis (ALS) risk. Methods We included participants from 5 large cohort studies-The Nurses' Health Study, the Health Professionals Follow-up Study, the Cancer Prevention Study II Nutrition, the Multiethnic Cohort Study, and the Women's Health Initiative-and identified 275 individuals who developed ALS during follow-up. Two controls were randomly selected for each case, matche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…A later epidemiological study attempted to address the relationship between prediagnostic BCAA levels and ALS in a population cohort but found no evidence of a significant relationship. 78 It should be noted that the only relationship in this study with a risk ratio >1 indicating a possible positive association with the development of ALS, was for serum isoleucine measured less than 5 years before ALS was diagnosed. In addition, this study included only 275 individuals who developed ALS, whereas our MR experiments aggregated data from a minimum of 12 577 ALS patients; it is, therefore, possible that the population cohort study was underpowered.…”
Section: Discussionmentioning
confidence: 50%
“…A later epidemiological study attempted to address the relationship between prediagnostic BCAA levels and ALS in a population cohort but found no evidence of a significant relationship. 78 It should be noted that the only relationship in this study with a risk ratio >1 indicating a possible positive association with the development of ALS, was for serum isoleucine measured less than 5 years before ALS was diagnosed. In addition, this study included only 275 individuals who developed ALS, whereas our MR experiments aggregated data from a minimum of 12 577 ALS patients; it is, therefore, possible that the population cohort study was underpowered.…”
Section: Discussionmentioning
confidence: 50%
“…We found that ALS-associated essential nutrients were concentrated in polyunsaturated fatty acids and fat-soluble vitamins, providing supportive evidence of the importance of lipid metabolism in ALS. No evidence has shown that diet-derived circulating essential amino acids and minerals influence the risk of ALS in the general population, even though some of them (e.g., branched-chain amino acids [ 77 ], iron, zinc, and selenium [ 78 ]) have attracted widespread attention. However, our research has certain limitations.…”
Section: Discussionmentioning
confidence: 99%
“…High doses of BCAAs over an extended period led to increased excitability in cultured cortical neurons and pyramidal neurons from the motor cortex slices of mice, suggesting a shared phenotype between neurons treated with BCAAs and neurons from genetic ALS mouse models [ 109 ]. However, a recent study investigating pre-diagnostic plasma levels of BCAAs from five extensive cohort studies did not find any association between these compounds and the risk of ALS [ 110 ].…”
Section: Amyotrophic Lateral Sclerosismentioning
confidence: 99%